2004
DOI: 10.14507/epaa.v12n5.2004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Academic Development in Catholic versus Non-Catholic Private Secondary Schools

Abstract: Utilizing hierarchical linear models, this study of 144 private schools (72 Catholic and 72 non-Catholic schools) drawn from the National Education Longitudinal Study of 1988 discovered that Catholic school students scored lower in reading than students at non-Catholic private schools. Analysis of internal school characteristics suggested that lower growth in reading achievement might be related in part to lower student morale in Catholic schools. However, we found no significant differences between Catholic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Catholic school effects have been well supported in school sector research in general (Coleman and Hoffer 1987;Bryk et al 1993) and have been demonstrated in civic participation studies (Campbell 2002 andSikkink 2003). One speculative possibility could be the significant changes Catholic schooling is undergoing on a number of levels, especially demographically, that may have effects on other outcomes (Kim and Placier 2004;Smith 2005;Meyer 2007). It is also possible that the Catholic school effect on civic socialization does not persist into adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Catholic school effects have been well supported in school sector research in general (Coleman and Hoffer 1987;Bryk et al 1993) and have been demonstrated in civic participation studies (Campbell 2002 andSikkink 2003). One speculative possibility could be the significant changes Catholic schooling is undergoing on a number of levels, especially demographically, that may have effects on other outcomes (Kim and Placier 2004;Smith 2005;Meyer 2007). It is also possible that the Catholic school effect on civic socialization does not persist into adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the higher the ENTER, the smaller the difference. It is also interesting to note, however, that Kim and Placier (2004) did not find any differences between Australian Catholic and non-Catholic private schools.…”
Section: Theoretical Frameworkmentioning
confidence: 90%
“…Yet, they also found that independent private schools did not enhance student achievement any more than did public schools. More recently, Kim and Placier (2004) found significant differences in a subsample of 144 private schools in the NELS data, with non-Catholic schools outperforming Catholic schools in reading but not in mathematics.…”
Section: Research On Public and Private Schoolsmentioning
confidence: 99%